TINJAUAN PENETRASI INDEKS ASPAL PERHADAP PENAMBAHAN LIMBAH POME - Alfian Saleh; Muthia Anggraini (LPPM Universitas Abdurrab, 2020)
Asphalt is an aggregate binding material in road pavement construction that plays a very important role in determining pavement performance although its composition is around 4-10% based on the total weight of the mixture. One effort that can be done to overcome these problems is to reduce dependence on oil asphalt by developing alternative binders. The addition of pome waste to asphalt becomes an alternative as a binding agent that can bind aggregates to asphalt pavement which is determined at the penetration value and asphalt softening point. In this study the penetration value and softening point without adding pome waste were 62.2 mm and 48.5 Â° C then pome waste was added by 1%, 2%, 3%, 4% and 5%. From the addition of this pome waste to the penetration value has decreased while for the softening point with the addition of this pome waste has increased. For the penetration value of the index with the addition of pome waste, the penetration value of the index has increased from -0,686 for asphalt without the addition of pome waste increased to -0,245 at 5% addition, this indicates that the addition of pome waste makes the asphalt sensitive to temperature.